Skrining Fitokimia dan Karakterisasi Minyak Biji Kemiri (Aleurites moluccana L.): Phytochemical Screening and Characterization of Candlenut Seed Oil (Aleurites moluccana L.) - Muhammad Azril Rizqullah; Abdul Rahim; Lizma Febrina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2023)
Candlenut is an intriguing plant, especially for its activities as a hair strengthener and its antibacterial properties. Various techniques can be employed to obtain candlenut oil, one of which is the roasting method. This method is cost-effective and easy to perform. However, there is currently no information on the phytochemical composition of candlenut oil produced using the roasting method. The aim of this research is to identify the groups of chemical compounds present in candlenut oil and to characterize candlenut oil. The research methodology for screening the phytochemicals in candlenut oil includes testing for alkaloids, flavonoids, steroids/terpenoids, tannins, phenols, and saponins. Characterization of candlenut oil includes organoleptic tests, water content analysis, acid value determination, saponification value determination, and density testing. The phytochemical screening results indicate that candlenut oil contains alkaloids, flavonoids, and steroids. The characterization results for candlenut oil reveal that it has a yellow color, smooth texture, and a distinctive candlenut oil scent. The water content is 0.01%, the acid value is 5%, the saponification value is 184.1825 mg KOH/g, and the density is 1.03 g/mL. This result shows that the obtained candlenut oil meets the Indonesian National Standard (SNI) for oil. Keywords: Candlenut, Phytochemical screening, Characterization Abstrak Kemiri merupakan tanaman yang menarik, khususnya aktivitasnya sebagai penguat rambut serta aktivitas antibakterinya. Berbagai teknik dapat dilakukan untuk mendapatkan minyak biji kemiri, salah satunya dengan metode sangrai. Metode ini merupakan metode yang murah dan mudah dilakukan. Namun belum ada informasi fitokimia terhadap minyak kemiri yang dihasilkan dengan metode sangrai. Tujuan dari penelitian ini untuk mengetahui golongan senyawa kimia yang terkandung pada minyak biji kemiri dan mengkarakterisasi minyak biji kemiri. Metode penelitian skrining fitokimia minyak biji kemiri meliputi alkaloid, flavonoid, steroid/ terpenoid, tannin, fenol, dan saponin. Karakterisasi minyak biji kemiri meliputi uji organoleptik, uji kadar air, uji bilangan asam, uji bilangan penyabunan, dan uji massa jenis. Hasil skrining fitokimia menunjukkan bahwa minyak biji kemiri mengandung golongan senyawa alkaloid, flavonoid, dan steroid. Hasil yang diperoleh dari karakterisasi minyak biji kemiri yaitu dari organoleptik minyak biji kemiri berwarna kuning, tekstur licin dan berbau khas minyak kemiri, kadar air 0,01%; bilangan asam 5%; bilangan penyabunan 184,1825 mg KOH/ g; massa jenis 1,03 g/ mL. Hasil ini memperlihatkan bahwa minyak biji kemiri yang diperoleh telah sesuai dengan standar SNI minyak. Kata Kunci: Kemiri, Skrining Fitokimia, Karakterisasi